Soft Pneumatic Actuator Skin with Piezoelectric Sensors for Vibrotactile Feedback - Sonar, Harshal Arun; Paik, Jamie (Frontiers in Robotics and AI, 2016)
The latest wearable technologies demand more intuitive and sophisticated interfaces for communication, sensing, and feedback closer to the body. Evidently, such interfaces require flexibility and conformity without losing their functionality even on rigid surfaces. Although there has been various research efforts in creating tactile feedback to improve various haptic interfaces and master-slave manipulators, we are yet to see a comprehensive device that can both supply vibratory actuation and tactile sensing. This paper describes a soft pneumatic actuator (SPA) based, SPA-skin prototype that allows bidirectional tactile information transfer to facilitate simpler and responsive wearable interface. We describe the design and fabrication of a 1.4 mm-thick vibratory SPA - skin that is integrated with piezoelectric sensors. We examine in detail the mechanical performance compared to the SPA model and the sensitivity of the sensors for the application in vibrotactile feedback. Experimental findings show that this ultra-thin SPA and the unique integration process of the discrete lead zirconate titanate (PZT) based piezoelectric sensors achieve high resolution of soft contact sensing as well as accurate control on vibrotactile feedback by closing the control loop.